Sistema web para la gestión de procesos de pasantías y prácticas preprofesionales - Tenecota Uyaguari, Jefferson Andres (2017)
The process automation in the Higher Education Institutions (HEIs) in Ecuador are part of the parameters that guarantee the quality of the services provided in these institutions. One of the components that work at the Technical University of Machala (UTMACH) is Preprofessional Internships / Practices. In this component, the creation and approval of Pre-professional Internship / Internship programs, start of Pre-professional Internship / Internship management within each career, creation of applications for Pre-professional Internships / Internships by students and approval by the Career coordinators, assignment of tutors to students, registration of on-site supervision, registration of tutorials, registration of daily activities by students and monthly reports of tutors.   At present, the UTMACH does not have a system that automates the processes mentioned, but that they control with the Microsoft office automation program Excel. The use of this type of tools does not allow to obtain updated information in real time, to cover this requirement, through this titling work is proposed to develop a web system that manages in an automated way the processes previously mentioned.   For the development of the web system we analyzed the different proposals existing among them the most popular programming languages ​​for web development like PHP, ASP.NET, Python, Ruby, Node.js. After comparing the different technologies Python was selected as a programming language and Postgres as a database since Python is a programming language that allows me to have an easy-to-understand syntax, is multiplatform, object oriented, simple and fast to program , Besides possessing a great variety of frameworks that agilitan the web development, between which Django was chosen since it allows the fast development and a clean design, as for Postgres its stability, scalability and besides being free, turn it into the best choice .   This type of software development projects requires a very good communication between the developers and the users for a constant presentation of advances and receipt of comments by the client, in this case the end users. For this reason, the methodology that applies perfectly is eXtreme Programming. This methodology, despite being one of the oldest is also one of the most robust and most used worldwide, it has developed many others.    Several meetings were held for the presentation of progress with the directors of the Directorate of Linkage, Cooperation, Internships and Practices, and members of the UTMACH Information and Communications Technologies Division participated in the meetings. The system is developed to be absolutely compatible with other systems implemented in the university and from which information will be obtained.